2021
DOI: 10.1007/s00384-021-03870-5
|View full text |Cite
|
Sign up to set email alerts
|

Effective dissection for rectal cancer with lateral lymph node metastasis based on prognostic factors and recurrence type

Abstract: Purpose There are no reports showing the significance and effective range of dissection for patients with lateral lymph node metastasis (LLNM). This study aimed to investigate the indications for lateral lymph node dissection (LLND) in patients with LLNM based on prognostic factors and recurrence types. Methods We reviewed 379 patients with advanced rectal cancer who were treated with total mesorectal excision plus LLND. We analyzed background factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The incidence of ILN metastasis from rectal and anal canal adenocarcinoma is 2.0%-4.5% [10,11] The results mentioned above might be attributed to the fewer haematogenous recurrences in our patients with ILN metastasis than in those with lateral LN metastasis in previous studies [25,28,32].…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The incidence of ILN metastasis from rectal and anal canal adenocarcinoma is 2.0%-4.5% [10,11] The results mentioned above might be attributed to the fewer haematogenous recurrences in our patients with ILN metastasis than in those with lateral LN metastasis in previous studies [25,28,32].…”
Section: Discussionsupporting
confidence: 48%
“…However, patients with ILN metastases from anorectal carcinoma were considered to have no worse a prognosis than patients with positive lateral LN metastasis, based on reports that showed a 5‐year overall survival rate of 25%–40% in patients with low rectal carcinoma showing lateral spread [27–31]. The results mentioned above might be attributed to the fewer haematogenous recurrences in our patients with ILN metastasis than in those with lateral LN metastasis in previous studies [25, 28, 32]. Moreover, ILN metastasis may be a more local disease than lateral LN metastasis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The survival benefits of LPND for patients with LPN metastasis depend on whether the local metastases can be cured by resection or if there is distant metastases that cannot be controlled locally. Previous studies confirmed that the location (5,13,21) and the number of LPN metastases (19,(22)(23)(24) are factors that affect the efficacy of LPND in patients with LPN metastases. In the present study, multivariate analysis demonstrated that lymph node metastasis to the common iliac or external iliac artery was an independent adverse prognostic factor for patients with LPN metastasis, with low 3-year OS and RFS rates.…”
Section: Discussionmentioning
confidence: 78%
“…Kanemitsu et al conducted a retrospective study involving 1,191 patients from two high-volume centers in Japan, and the results showed that the survival benefits from LPND of the internal iliac and obturator areas were comparable to those obtained through dissection of the superior rectal artery area (13). Similarly, Morohashi et al reported that lymph node metastasis outside the internal iliac and obturator lymph node area was an independent prognostic risk factor for patients with LPN metastasis (HR: 2.70; 95% CI, 1.20-6.08; P = 0.016) (21). The above literature is consistent with our study results, suggesting that external iliac or common iliac lymph node metastasis could be regarded as a systemic disease and that prognosis cannot improve even with dissection But that leads to increased urinary and sexual dysfunction; thus, the systemic comprehensive therapy should be strengthened to replace LPND.…”
Section: Discussionmentioning
confidence: 88%